Factors Influencing Fraud Detection: Internal Audit, Human Resource Competency and Morality Culture - Abdul Halim Harahap; Cris Kuntadi (Sean Institute, 2024)
Previous research or relevant studies play a crucial role in building the theoretical foundation and hypotheses for future research. This article aims to review the factors influencing the detection of errors and fraud, focusing on the Role of Internal Audit, Human Resource Competency, and Morality Culture. The Role of Internal Audit reflects the auditor's ability to perform their duties objectively and free from internal organizational interests. Human Resource Competency ensures that organizational members are equipped with the necessary skills to identify and report fraud effectively, while a strong Morality Culture supports an environment where honesty and integrity are valued, motivating members to act without fear of reprisal. With an in-depth understanding through this article, it is expected to generate strong hypotheses about the relationship between these factors in the context of detecting errors and fraud, which can help improve the effectiveness of fraud prevention and detection efforts in various sectors and organizations. The results of this literature review article are: 1) The Role of Internal Audit affects the Detection of Errors and Fraud, 2) Human Resource Competency affects the Detection of Errors and Fraud, and 3) Morality Culture affects the Detection of Errors and Fraud.